Deadpool: all in the family ebook - Various, Marvel (Marvel Worldwide, Inc., 2024)
Collects Cable (2008) #25, Deadpool & Cable (2008) #26, Deadpool Family #1. CHILL as Lady Deadpool and Headpool undergoe invasive analysis to ferret out the root cause of their majorly abusive frenemieship. THRILL as Kidpool and Dogpool embark on a 100-ton mechanized joyride. And…um…GET ILL as Dogpool makes a brand-new archenemy. Enter: Voidmutt! Then, it's 'Two Mutants and a Baby' in the untold story of how Cable escaped from Alaska with Hope. Wait — you didn't think Cable did that alone, did you? Hell no. He asked for help from his favorite Merc with a Mouth. And finally, Deadpool struggles to find the perfect way to honor his fallen mutant pal when he remembers Rumekistan, the troubled and totally fictional European country Cable once tried to turn into a Utopia on earth. It's the perfect place for a Cable museum! A Cable amusement park! A Cable cable TV show!